2022
DOI: 10.1113/jp282954
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β1 impairs the transcriptomic response to contraction in myotubes from women with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is characterised by a hormonal imbalance affecting the reproductive and metabolic health of reproductive‐aged women. Exercise is recommended as a first‐line therapy for women with PCOS to improve their overall health; however, women with PCOS are resistant to the metabolic benefits of exercise training. Here, we aimed to gain insight into the mechanisms responsible for such resistance to exercise in PCOS. We employed an in vitro approach with electrical pulse stimulation (EPS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…For our study, we analyzed three distinct microarray datasets from the Gene Expression Omnibus (GEO) database hosted by the NCBI. These datasets corresponded to PCOS, endometrial cancer, and ovarian cancer, identified by the accession numbers GSE199225[12], GSE215413[13], and GSE174670[14], respectively. Our selection criteria included considering only complete samples categorized as either cases or controls.…”
Section: Methodsmentioning
confidence: 99%
“…For our study, we analyzed three distinct microarray datasets from the Gene Expression Omnibus (GEO) database hosted by the NCBI. These datasets corresponded to PCOS, endometrial cancer, and ovarian cancer, identified by the accession numbers GSE199225[12], GSE215413[13], and GSE174670[14], respectively. Our selection criteria included considering only complete samples categorized as either cases or controls.…”
Section: Methodsmentioning
confidence: 99%
“…NGS dataset GSE199225 [25] was acquired from the GEO database. The GSE199225 profile was composed of 30 PCOS samples and 30 normal control samples.…”
Section: Methodsmentioning
confidence: 99%
“…We chosen NGS dataset GSE199225 [25] from Gene Expression Omnibus (GEO) (https://www.ncbi.nlm.nih.gov/geo/) [26] database. We then applied for DESeq2 package in R software to obtain the differentially expressed genes (DEGs) in the NGS dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies examined the transcriptome after EL-EPS in primary human myotubes (25,26). Genes related to pro-inflammatory pathways were upregulated in myotubes originating from females with polycystic ovary syndrome relative to healthy controls (25).…”
Section: D In Vitro Exercise and Transcriptomicsmentioning
confidence: 99%
“…Two recent studies examined the transcriptome after EL-EPS in primary human myotubes (25,26). Genes related to pro-inflammatory pathways were upregulated in myotubes originating from females with polycystic ovary syndrome relative to healthy controls (25). Although EL-EPS responses may be affected by donor characteristics (1,3), a recent study suggests that age, sex, and EL-EPS parameters may not have substantial transcriptomic and proteomic effects (26).…”
Section: D In Vitro Exercise and Transcriptomicsmentioning
confidence: 99%